Impact of Endurance Testing on the Thermal Performance of a Retrofitted FDM 3D Printer - Alexander Ariantono Nugroho; David Christanto; Laurentius Yudha Bramantyo; Bondan Wiratmoko Budi Santoso; Ign. R. Haryosuprobo; Mardiatno (Mechanical Engineering Department - Semarang State Polytechnic, 2026)
The reliability of retrofitted Fused Deposition Modeling (FDM) 3D printers is affected by thermal stability during long print cycles. This study evaluated the thermal performance of a retrofitted BFB 3D Touch Cartesian FDM printer equipped with dual extruders, automatic bed leveling, a BTT SKR v1.4 controller, and a 24 V/360 W power supply unit (PSU). An 80 × 80 × 80 mm calibration cube was printed for 5 h to impose a continuous thermal load. Surface temperatures of stepper drivers, stepper motors, mainboard, PSU, and heated bed were measured with a TR-10 thermal imager at 1 h intervals, while bed preheating was recorded for 7 min at P1-P4 and the bed center. The Y1 driver reached 68.7 °C at hour 3, the PSU reached 65.0 °C at hour 5, and the extruder motor reached 52.7 °C. The bed center reached 59.2 °C at minute 7, but the corner regions were lower and locally non-monotonic. These fluctuations are interpreted as effects of local heat-transfer non-uniformity and measurement instability rather than uniform bed cooling. This study shows that driver and PSU cooling, cable-size verification, repeated measurements, and bed insulation are required to improve retrofit-printer reliability in extended operation.